Factors Affecting Elderly Patient Satisfaction with Services in the Emergency Department: A Systematic Review - Prianto Nugroho, Fajar; M. Ramdan, Iwan; Riyaningsih, Riyaningsih (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : With the increasing number of older adults, quality care in the ED is critical as the first port of call for emergency care, influencing the satisfaction and health outcomes of older patients. The aim of this systematic review is to identify and analyze the various factors that influence older adults' satisfaction with ED care. Objective : The purpose of this systematic review is to identify and analyze the various factors that influence elderly satisfaction with services in the emergency department. Research Methods/ Implementation Methods : The study followed PRISMA 2020 standards, examining English-language literature from 2014 to 2024. The study excluded editorials, reviews from the same journal, and submissions without DOIs. PubMed, SagePub, SpringerLink, and Google Scholar were used as literature sources. Results : Initially obtaining 360 articles from online databases (PubMed, SagePub, SpringerLink, and Google Scholar), eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion/Lesson Learned : Elderly satisfaction with emergency department services is influenced by demographic, service, environmental, psychological factors, and patient involvement in decision making. Good communication, reduced waiting times, and the creation of an elderly-friendly environment are important to improve the experience and health outcomes of elderly patients in the emergency department.